Hypotheses Verification for High Precision Cohesion Metric - Kayarvizhy N,; Kanmani S,; Rhymend Uthariaraj V, (International Journal of Computer Sciences and Engineering, 2014)
Metrics have been used to measure many attributes of software. For object oriented software, cohesion indicates the level of binding of the class elements. A class with high cohesion is one of the desirable properties of a good object oriented design. A highly cohesive class is less prone to faults and is easy to develop and maintain. Several object oriented cohesion metrics have been proposed in the literature. In this paper, we propose a new cohesion metric, the High Precision Cohesion Metric (HPCM) to overcome the limitations of the existing cohesion metrics. We also propose seven hypotheses to investigate the relationship between HPCM and other object oriented metrics. The hypotheses are verified with data collected from 500 classes across twelve open source Java projects. We have used Pearsonï¿½s coefficient to analyze the correlation between HPCM and the metrics in the hypotheses. To further bolster our results we have included p-value to confirm the statistical significance of the findings.